Evaluating the bond durability of FRP-concrete systems subjected to environmental exposures - Mata Carrillo, Oscar Rafael, author; Atadero, Rebecca, advisor; Heyliger, Paul, committee member; Glick, Scott, committee member (Colorado State University. Libraries, 2012)
The poor current condition of transportation infrastructure in the U.S. is well documented. With traffic volumes on the rise, as well as limited funding available to maintain and rehabilitate aging bridges, cost effective means of improving the performance and durability of these structures must be employed. Fiber Reinforced Polymers (FRPs) offer one potential solution. Their use has been progressively growing in the field of civil engineering as the material's high strength to weight ratio, non-corrosive nature, and ability to conform to existing geometry make it appealing in the reinforcement of existing reinforced concrete structures. In most applications of FRP to strengthen an existing structure, the FRP-concrete bond is essential. Bond is needed for proper transfer of stresses among interfaces. From a durability standpoint, the long-term bond performance is also a major concern. As a result, a long-term durability study was conducted in the laboratory to evaluate the behavior of the bond between the FRP and concrete. Small concrete specimens were prepared, reinforced with FRP material, and subjected to various environmental scenarios such as wet-dry cycles, freeze-thaw cycles, and constant immersion in water, as well as deicing agents. Direct tension pull-off tests and three-point flexural tests were conducted on these specimens to determine any degradation in bond strength over time. Finally, the pull-off test method was evaluated by means of previous research studies and recommendations about preparation procedures were made.
Keywords: bond; pull off tests; FRP; durability; concrete